PROBLEMATIKA PENGEMBANGAN KURIKULUM SDLB BHAKTI LUHUR MALANG - Nini, Klemensia (Jurnal Pelayanan Pastoral, 2021)
The curriculum in its implementation continues to change. The change indicates that the nature of the curriculum itself is not stagnant but dynamic following the development of science and technology. The impact of the development of science and technology can occur in all lines of people's lives. The needs and demands in the wider community inevitably change as changes and developments occur. Changes in the education curriculum in regular educational institutions, inclusion, and special education intend that the national education goals contained in Law No. 20 of 2003 can be achieved properly. As we know that children with certain special needs require a lot of adjustment because between one individual and other individuals have different abilities. To overcome this diversity, educators are obliged to make modifications to each category. In the efforts to develop a curriculum various problem must have sprung up. The problem of SDLB curriculum development has not been widely researched so this research is focused more on exploring the problems faced by educators of children with special needs at the elementary school level. The types of research used are qualitative types of case study design and interactive data analysis models Miles and Huberman. The subjects of the study were 4 teachers of SDLB Bhakti Luhur Malang. The main instrument is the human instrument. Supporting instruments use interview guidelines, recording tools, and observation guidelines. Miles and Huberman's model interactive data analysis step is 1) data reduction 2) data display 3) conclusion drawing/verification. The results of this study show that curriculum development problems include development models, student complexity, connectivity, curriculum development team resources.